2020
DOI: 10.1111/mam.12192
|View full text |Cite
|
Sign up to set email alerts
|

Employing statistical learning to derive species‐level genetic diversity for mammalian species

Abstract: 1. The patterns of genetic diversity in several genomic regions have been used in mammalian systematics for decades. For instance, when studying closely related species, it is generally assumed that the mitochondrial cytochrome b gene (cytb) exhibits significant information that can be used for differentiation between intraspecies and interspecies variation in mammals. Because of sampling limitations, early analyses of this proposition were conducted mainly on rodents and bats. 2. Currently, more than 57000 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Transient pieces of cartilaginous tissues in young specimens of muroid rodents have been reported before, for example in Peromyscus eremicus ( Spotorno, 1992 ) and plantar-pad polymorphisms have been previously reported for sigmodontines ( e.g ., Musser et al, 1998 : 58). Cytb divergence between specimens from Colombia and Ecuador at 2.8% is well-within reported intraspecific divergence for sigmodontine rodents and other mammals ( Allen et al, 2020 ; Schrago & Mello, 2020 ).…”
Section: Appendixsupporting
confidence: 79%
“…Transient pieces of cartilaginous tissues in young specimens of muroid rodents have been reported before, for example in Peromyscus eremicus ( Spotorno, 1992 ) and plantar-pad polymorphisms have been previously reported for sigmodontines ( e.g ., Musser et al, 1998 : 58). Cytb divergence between specimens from Colombia and Ecuador at 2.8% is well-within reported intraspecific divergence for sigmodontine rodents and other mammals ( Allen et al, 2020 ; Schrago & Mello, 2020 ).…”
Section: Appendixsupporting
confidence: 79%
“…GenBank has a far greater scope of genetic markers (Porter and Hajibabaei 2018), but because there is currently no possibility to correct or even flag problematic species assignation of sequences, it may actually become increasingly misleading to rely on it for automatized barcoding approaches (Shen et al 2013). For instance, in a recent review evaluating species-level genetic diversity for mammalian species based on CYTB, Schrago and Mello (2020) provided practical guidelines to improve the performance of unsupervised algorithms for species delimitation. To highlight species deserving attention for possible cryptic lineages, they give the example of the endangered M. atacamensis showing "unusually high genetic differences" in that Neotropical species, overlooking the fact that one of the two reference sequences taken from the Genbank (MF143493; Platt et al 2018) is actually a mislabelled M. muricola (see Online Resource 1), hence inflating their "intra-specific" statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Our estimated percentage of divergence in mtDNA between clade A (D. bozinovici, hereafter) and the other clades (range: 7.3-12%) is comparable with what Himes et al (2008) reported (range: 11.3-15%). While these authors did not attribute these divergences to a major split in the Dromiciops lineage, these levels of divergence are typical for inter-specific variation in mammals (Baker & Bradley, 2006;Schrago & Mello, 2020), and led D'Elia et al (2016) to revisit the problem and designing clades A and B to the level of species (Table 5). In contrast, Suárez-Villota et al (2018), analyzing four nuclear and two mtDNA markers in Dromiciops individuals from 20 localities reported genetic distances (K2P) averaged across all loci that were an order of magnitude lower (on the range of 0.001 to 0.015%) and concluded that these differences were within the intra-species range previously reported for other marsupials.…”
Section: Discussionmentioning
confidence: 99%